2006
DOI: 10.1002/jssc.200600002
|View full text |Cite
|
Sign up to set email alerts
|

Isotope‐ratio detection for gas chromatography

Abstract: Isotope-ratio detection for gas chromatographyInstrumentation and methods exist for highly precise analyses of the stable-isotopic composition of organic compounds separated by GC. The general approach combines a conventional GC, a chemical reaction interface, and a specialized isotoperatio mass spectrometer (IRMS). Most existing GC hardware and methods are amenable to isotope-ratio detection. The interface continuously and quantitatively converts all organic matter, including column bleed, to a common molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
277
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(288 citation statements)
references
References 90 publications
(139 reference statements)
6
277
0
5
Order By: Relevance
“…, 2002, 2006. However, the data presented in CHAPTER 5 only represent a snapshot in time and considerable time series studies must be conducted before such hypotheses can be validated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2002, 2006. However, the data presented in CHAPTER 5 only represent a snapshot in time and considerable time series studies must be conducted before such hypotheses can be validated.…”
Section: Discussionmentioning
confidence: 99%
“…The trends presented by SHERWOOD LOLLAR et al (2002, 2006, 2008 have not been observed in purported abiogenic hydrocarbons from higher temperature settings (Figure 4.8), such as those present in vent fluids of the Lost City hydrothermal site or those formed in abiotic synthesis experiments (FU et al, 2007), leading to speculation that this reflects mechanistic differences. Based on the experimental observations of reversible exchange presented here, this discrepancy may actually reflect partial or complete alkane-water H isotope exchange in the latter cases.…”
Section: H / 1 H Ratios and Abiogenesis In Igneous Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, high-precision isotope ratios have a special place in chemistry, especially in geochemistry, for determining reaction mechanisms and providing formation histories (1). Currently, the most commonly used instruments for determining high-precision isotope ratios are special-purpose isotope-ratio mass spectrometers (IRMS) (2,3) that are fairly costly, require experts to operate and maintain, and are not portable-facts that have limited significantly the applicability of light stable isotope ratio measurements despite the technological advances achieved with online sample introduction and combustion for compound-specific isotope analysis (CSIA) (4).…”
mentioning
confidence: 99%
“…Generally, the shotnoise ratio is larger for N 2 O than for CO 2 due to the lower abundances of the rare isotope (1.1 % 13 C, 0.37 % 15 N and 0.201 % 18 O, e.g. Sessions, 2006) and the signal intensity of N 2 O as compared to CH 4 -induced CO 2 , due to lower mixing ratios (e.g. Schilt et al, 2010) and ionization efficiency (Friedli and Siegenthaler, 1988;Ghosh and Brand, 2004).…”
Section: Shot Noisementioning
confidence: 99%